Network sonification from observational data: Another way of listening to the complexity of public space (REVISTA NODO, 2023)
The future of public spaces is one of the debates currently capitalizing on reflection on reflections about the future of the city in the new millennium. At the heart of this discussion lies the idea of urban space as the result of a system in which environmental variables (space design), social variables (population profiles) and psychological variables (uses and behaviors) intersect. Such complexity requires adequate analysis systems as well as straightforward ways to easily and rigorously represent the data obtained. This article analyses the dynamics of a square in Barcelona at two different times based on data obtained through systematic observation. This data will be analyzed as a network using Network Analysis (AR) procedures. The data will be also sonified to extract information about their dynamics. For this purpose, the relationships between the nodes are converted into chord sequences that enable differentiated sound marks to be established for each moment analyzed. The joint use of AR and data sonification allow for procedures in which visualization and listening complement each other to analyze socio- spatial dynamics, while offering an interesting aesthetic result.